Toolkit for Developing Skills and Capacity in Applying Foresight to Climate Resilient Agricultural Development in the SADC Region. Module 5: Scenario Implications and Transformational Change - Chesterman, Sabrina; Neely, Constance; Gosling, Amanda; Quinn, Claire; Chevallier, Romy; Lipper, Leslie; Thornton, Philip K. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
The SADC Futures project has developed a range of foresight training materials. The SADC Futures Foresight Training Toolkit forms part of this knowledge series and presents content that was given during the SADC Futures webinar series, a six-part virtual webinar series and facilitated training.